2001
DOI: 10.1073/pnas.081078898
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two active branches for electron transfer in photosystem I

Abstract: All photosynthetic reaction centers share a common structural theme. Two related, integral membrane polypeptides sequester electron transfer cofactors into two quasi-symmetrical branches, each of which incorporates a quinone. In type II reaction centers [photosystem (PS) II and proteobacterial reaction centers], electron transfer proceeds down only one of the branches, and the mobile quinone on the other branch is used as a terminal acceptor. PS I uses iron-sulfur clusters as terminal acceptors, and the quinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
291
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(319 citation statements)
references
References 30 publications
25
291
3
Order By: Relevance
“…The absorption changes associated with reoxidation of PhQ are described by two exponential decay components (18,19). The fact that point mutations near PhQ A or PhQ B resulted in changes in the rates of either the slower ( Ϸ 200 ns) or faster ( Ϸ 20 ns) components, respectively (3,5), are most easily interpreted in terms of a bidirectional model, in which ET occurs with a given probability in either the A-or B-branch, resulting in reduction of PhQ A or PhQ B , respectively. This model predicts that the amplitudes of the two components are determined by the relative use of each branch, and the observation that mutations in neither PhQ-binding site observably changed these amplitudes argues in favor of this interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption changes associated with reoxidation of PhQ are described by two exponential decay components (18,19). The fact that point mutations near PhQ A or PhQ B resulted in changes in the rates of either the slower ( Ϸ 200 ns) or faster ( Ϸ 20 ns) components, respectively (3,5), are most easily interpreted in terms of a bidirectional model, in which ET occurs with a given probability in either the A-or B-branch, resulting in reduction of PhQ A or PhQ B , respectively. This model predicts that the amplitudes of the two components are determined by the relative use of each branch, and the observation that mutations in neither PhQ-binding site observably changed these amplitudes argues in favor of this interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…The two mutations would have to shift the equilibrium without noticeably changing either PhQ reoxidation rate. Conversely, mutations of the Trps adjacent to the PhQs, PsaA-Trp-697 and PsaB-Trp-677, would have to affect the rate constants in such a way that only one of the observed rates is altered without changing the relative amplitudes of the two phases (3,5).…”
Section: Discussionmentioning
confidence: 99%
“…The transmission changes (⌬I/I) were corrected for the contribution of plastocyanin, determined at 870 -950 nm (34), but using an optimized new generation pulse amplified modulation (PAM) system (Dual-PAM, plastocyanin-P 700 version, Heinz Walz, Effeltrich, Germany), which allows simultaneous determination of the difference transmission signals arising from plastocyanin and P 700 . 4 Using pre-illuminated Arabidopsis leaves with fully active Calvin cycle to avoid an acceptor-side limitation of PSI oxidation, P 700 and plastocyanin were pre-oxidized by 10-s illumination with weak far-red light selectively exciting PSI, followed by a strong saturating red light pulse (100-ms duration, 6000 mol m Ϫ2 s Ϫ1 ), resulting in complete photooxidation of P 700 and plastocyanin and their subsequent reduction after the end of the light pulse. The maximal transmission changes between fully oxidized and fully reduced states were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The two branches of the PSI electron transfer chain are not structurally equivalent and differ in their lipid association: Whereas phosphatidylglycerol is found in close proximity to one of the branches, monogalactosyldiacylglycerol is associated with the other branch (2). It is presently unclear whether these branches are active to similar extents (4,5). Phylloquinone (vitamin K 1 ) is an essential component of the human diet, because it serves as a cofactor for ␥-carboxylation of glutamyl residues in different proteins, such as blood coagulation factors, but cannot be synthesized in animals and humans (6).…”
mentioning
confidence: 97%
“…The in vivo analysis of the kinetics of electron transfer from the quinone to F X revealed two kinetic components (Joliot and Joliot, 1999). By mutating quasi symmetrical residues of PsaA and PsaB near the quinone, it was found that a particular mu-tation in one branch affected the faster component, whereas an analogous mutation in the other branch affected the slower component, indicating that in striking contrast to photosystem II (PSII), both branches are active in PSI (Guergova-Kuras et al, 2001). It is not possible within this short review to mention the numerous studies performed with C. reinhardtii on the structure-function relationship of the other parts of PSI and on the other complexes PSII, the cytochrome b 6 f complex, the ATP synthase, and Rubisco (for details, see Hippler et al, 1998).…”
Section: Genetic Dissection Of Photosynthesismentioning
confidence: 99%